Developing interactive multimedia in enhancing students' listening comprehension using Moodle and Thinglink - Putri, Citra Anggia; Sari, Winda Setia; Tambunan, Anna Riana Suryanti (UNIB Press, 2024)
The effect of COVID-19 outbreak to education is in form of a shift of instructional practices from classroom-based instructions to online technology-based practices. To respond to the needs of technology-based instructional activities, this study developed interactive multimedia utilizing online technology-based platforms featuring Moodle and Thinglink to enhance students' comprehension in listening. This is a Research and Development involving fifty-three students of English literature study program in a state university in North Sumatera as object of the study. This study applies the ADDIE model to develop interactive multimedia learning. Purposive sampling was used to collect the samples for analysis. Tests, questionnaires, and interviews were designed and employed to collect the data. Material and media experts carried out the validation of the product. The paired samples t-test and independent samples t-test were utilized for data analysis. The outcomes are interactive multimedia using Moodle and ThingLink, complete with its tutorials, practices, and tests to boost the students' listening comprehension. Interactive multimedia featuring Moodle and ThingLink was deemed practical to use and effectively increased the students' listening comprehension according to the results of the material and media experts' validation and student response questionnaires.